PSYCHOANALYSIS IN JODI PICOULTS' MY SISTER'S KEEPER - Hana Safitri; Wilujeng Asih Purwani (Karangan: Jurnal Bidang Kependidikan, Pembelajaran, dan Pengembangan, 2022)
The study aims to analyze the students’ writing analytical exposition text in the pandemic era and the students’ responses leathe rning writing analytical exposition in pandemic era.  The design of study was content analysis (CA) that creating experiences from unstructured message content. The data collected were students’ writing, questionnaire and interview. The instrument of study was the writer itself. The data describe it by qualitative approach. The study conducted at SMAN 1 Karangbinangun Lamongan that subjects of study was XI IPA 1, XI IPA 2, XI IPA 3. It was about 10 students from each grade, it means 30 students.  The finding of study were 7 students were poor in grammar, 27 students were poor in vocabularies, 15 students were bad in organize the writing, 21 students were poor in mechanism in writing. Considering the finding are the most error in writing analytical exposition was the students’ vocabulary acquisition. The finding also supported by the students’ responses in learning writing analytical exposition which told that their error writing because of they were poor in vocabulary. It means that before teach the students in writing English, the teacher have to master the students’ vocabulary acquisitions.